The PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY PELANGGAN TRAVELOKA DI KOTA BANDUNG - Fahmi Adyan Abdurrahman; Trisha Gilang Saraswati (FEB Universitas Sam Ratulangi Manado, 2023)
Customer e-loyalty will appear along with company e-services quality. This study was conducted to analyze the effect of e-service quality on Traveloka customer e-loyalty in Bandung city. The purpose of this study was to find out how e-service quality affects traveloka customer e-loyalty in Bandung city. This study applies quantitative methods with descriptive and causal research types. The sample used is 100 respondents. Data analysis techniques apply descriptive analysis and simple linear regression. The results of the descriptive analysis study show that e-service quality and e-loyalty are in the good category. The results of simple linear regression show that e-service quality has a significant effect on e-loyalty for Traveloka customers in Bandung city.